A balanced UWB power divider based on parallel coupling slotlines with improved isolation. Issue 1 (29th October 2018) - Wei, Feng; Yang, Zhi‐Jie; Li, Bin; Shi, Xiao‐Wei
Abstract: A balanced‐to‐balanced ultra‐wide band (UWB) equal power divider (PD) based on parallel coupling slotlines is presented in this article. An ultra‐wide differential‐mode (DM) impedance bandwidth covering from 2.8 to 9.4 GHz can be achieved. It is noted that the DM performance is independent of the common‐mode (CM) response, which reduces the design complexity greatly. Meanwhile, CM response with a larger bandwidth and a higher suppression is obtained intrinsically. More importantly, two methods are designed and adopted to improve the DM isolation between the two output ports. To validate the correctness of the design method, a prototype circuit is fabricated and measured. The contrast of the simulated and measured results shows a good agreement.